GM-011 Centralised preparation of argatroban syringes: medico-economic assessment after 18 months. (24th March 2015) - Barral, M; Mounsef, F; Grasset, L; Brunel, P
Abstract : Background: Argatroban is indicated in cases of suspected type II heparin-induced thrombocytopenia (HIT) at a starting dose of 0.5 to 2 μg/kg/min (70 kg patient: dose between 50 and 201 mg/day). But argatroban is presented in vials of 250 mg/2.5 mL. So there is between 20% and 80% of waste. As argatroban is expensive and the presentation unsuitable, we decided in 2013 to centralise the reconstitution of the drug in the hospital pharmacy. One vial produces five 50 ml syringes ready to use, for multiple day use of argatroban 1 mg/ml, done under a biosafety cabinet with supervision, and in air controlled area. The firm validated the physicochemical stability of the preparation for 14 days and we validated the microbiological stability for 5 days. Purpose: After 18 months, what is the medico-economic assessment of this preparation? Material and methods: Retrospective, cost minimisation analysis from January 2013 until June 2014 for the hospital. We compared two Hypotheses (H): H1: cost of the reconstitution of argatroban at the pharmacy. One vial = 5 prepared syringes: preparation cost is estimated at €355 (including costs of one vial, consumables and staff); H2: if one vial was reconstituted daily on a ward (cost of one vial only included = €255.25 worst case: no staff, no consumables included). Results: 12 patients treated, average age 75 years ([66; 87]). Average duration of treatment: 16 days ([1; 40]). Average dosage: 0.53 mg/kg/min ([0.33; 1.07]) or 46 mg/day ([24; 61]). Total of 245 prepared syringes, 49 vials used. 9% (23/245) of prepared syringes were not administered. H1: cost €17, 395. H2: cost €56, 666 calculated on 222 vials (245 prepared syringes – 23 syringes not administered). Total savings = €39, 270. Average savings per patient €3, 272. Conclusion: To conclude, centralised preparation of argatroban syringes at the hospital pharmacy guarantees their safety, sterility and significantly reduces the cost of the treatment (reduction of 69%). As our next step, we aim to extend the time of microbiological stability (expiry date). References and/or acknowledgements: No conflict of interest.